A Needs Assessment of Choral Groups at an Archdiocesan Shrine in Tacloban City, Philippines: Basis for an Extension Project - Mabini, Jay P.; Macapaz, Nick John (Future Science / FSH-PH Publications, 2025)
This qualitative needs assessment explores the current practices, challenges, and developmental needs of the choirs serving at an Archdiocesan Shrine in Tacloban City. Utilizing a qualitative descriptive design, data were gathered through interviews and focus group discussions with ten purposively selected participants from choir members, coordinators, and conductors. Thematic analysis revealed five major themes: current musical practices, training and skill development needs, resource limitations, coordination and leadership, and spiritual and community growth. Findings indicate that while choirs exhibit strong commitment and structured rehearsal routines, they face significant gaps in formal training, access to musical resources, and leadership support. Participants also emphasized the choir’s role as a spiritual community and expressed a desire for deeper liturgical formation and pastoral guidance. These findings suggest the need for multidimensional interventions, including capacity-building initiatives, resource allocation, leadership development, and spiritual enrichment. The study further recommends the implementation of an extension project by the Leyte Normal University Bachelor of Music in Music Education, offering workshops and mentorship to address the identified needs. Strengthening the choir ministry is seen as essential not only for improving liturgical music quality but also for enhancing the spiritual vitality of the parish community.